Umedalen Skulptur 94. - Galleri Stefan Andersson, Umea (Umea : Umedalens skulpturpark, 1994)
Blomqvist, Andreas ; Borchgrevink, Hanne ; Breivik, Bard ; Carnemalm, Björn ; Ekman, Stina ; Engström, Urban ; Eriksson, Tina ; Fagerlund, Mikael ; Falk, Lars-Erik ; Gormley, Antony ; Gudmundsson, Sigurdur ; Gunnars, Carina ; Hydén, Acke ; Höste, Einar ; Kirschenbaum, Bernard ; Larsen, Lone ; Naraha, Takashi ; Nilsson, Jörgen ; Nobel, Jonas ; Rückriem, Ulrich ; Wretling, David ; Aberg, Mikael ; Ögren, Karin
biografie
Umedalen Skulptur 94, Umedalens skulpturpark, Umea, 28/5 - 11/9/1994
Zweeds
kunstcatalogus
Keywords: Umea